Emerging technologies and their potential for generating new assistive technologies - Abdi, Sarah; Kitsara, Irene; Hawley, Mark S.; de Witte, L. P. (Assistive technology, 2021)
Limited access to assistive technology (AT) is a well-recognized global challenge. Emerging technologies have potential to develop new assistive products and bridge some of the gaps in access to AT. However, limited analyses exist on the potential of these technologies in the AT field. This paper describes a study that aimed to provide an overview of emerging technological developments and their potential for the AT field. It involved conducting a gray literature review and patent analysis to create an overview of the emerging enabling technologies that may foster the development of new AT products and services and identify emerging AT applications. The analysis identified seven enabling technologies that are relevant to the AT field. These are artificial intelligence, emerging human-computer interfaces, sensor technology, robotics, advances in connectivity and computing, additive manufacturing and new materials. Whilst there are over 3.7 million patents related to these enabling technologies, only a fraction of them - 11,000 patents were identified in the analysis specifically related to AT (0.3%). The paper presents some of the promising examples. Overall, the results indicate that there is an enormous potential for new AT solutions that capitalize on emerging technological advances.